Developing methodologies for large scale wave and tidal stream marine renewable energy extraction and its environmental impact: An overview of the TeraWatt project - Harshinie Karunarathna (Ocean and Coastal Management, 2017)
Highlights•Licensing arrangements for marine renewable energy (MRE) developments must consider potential environmental effects.•These include the single, combined and cumulative effects of multi-site MRE developments over a wider region.•We introduce here a “toolbox” of datasets and methods to quantify the effects of wave and tidal stream MRE developments.•These were applied to the area of greatest MRE development potential in Scottish waters (Pentland Firth and Orkney Waters).